Uji Aktivitas Wound Healing Ekstrak Etanol Buah Averrhoa bilimbiL. (Belimbing Wuluh) pada Mencit Putih Jantan (Mus musculus) - Rahmayati Rusnedy; Mira Febrina; Cindy Patika Sari (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Wound healing is a complex process, delays in wound healing increase the chances of infection, improper healing, and unpleasant scarring. Belimbing wuluh (Averrhoa bilimbi L.) fruit contains various active compounds that are beneficial to health and have the potential to be used as medicinal preparations for treating wounds. In this test, incisions were made on the skin of the mice's back area using a scalpel 1 cm long and 0.3 cm deep. Observation of the length of the incision was carried out every day for 12 days using a caliper. Significant wound healing activity was observed from administration of 10% concentration of ethanol extract of belimbing wuluh (Averrhoa bilimbi L.) fruit which contains chemical compounds such as flavonoids, saponins, tannins and triterpenoids as well as minerals, one of which is zinc and Vitamin C is also proven to help speed up the healing process of incisions with a percentage of wound healing on day 12, which is 100%, the same percentage value as the group of test animals given Povidone Iodine 10% (Betadine®) as a comparator drug. The presence of zinc (zinc) and vitamin C in the extract of star fruit (Averrhoa bilimbi L.), is predicted to also contribute to the wound healing process in this test.